The quest for the SPIN transistor. - Zorpette, G.
Microelectronics researchers have been investigating spin for at least 20 years. Indeed, their discoveries revolutionized hard-disk drives, which since 1998 have used a spin-based phenomenon to cram more bits than ever on to their disks. Within three years, Motorola Inc. and IBM Corp. are expected to take the next step, introducing the first commercial semiconductor chips to exploit spin-a new form of random access memory called M (for magnetic) RAM. In this paper, the author describes how the mystical property of electron spin is revolutionizing the memory business. If it can do the same with logic, electronics will become "spintronics"
Keywords: MRAM; Electron spin; Magnetic RAM; Semiconductor chips; Spin transistor; Spintronics